A novel indicator for defining plain urban river network cyanobacterial blooms: resource use efficiency. Issue 10 (October 2022) - Su, Yifan; Gan, Lin; Li, Yun; Fan, Ziwu; Xie, Chen; Liu, Yang; Liao, Yipeng; Ding, Rui; Liu, Guoqin; Wu, Jingxiu; Chen, Guangyu; Sun, Jianhao; et al.
Abstract: Increasing eutrophication and climate change have led to heavy cyanobacterial blooms in water diversion sources (e.g., lakes, reservoirs), which can potentially cause algae-bearing water to spread to downstream to an urban river network via diversion channels. Defining the extent of cyanobacterial blooms in an urban river network has become a novel concern in urban river management. In this paper, we investigated the physicochemical and algae community characteristics of a small, closed, urban river network, JiangXinZhou (JXZ), in the Lake Taihu basin. We propose a novel indicator, resource use efficiency (RUE), for defining the extent of cyanobacterial blooms in JXZ, whose recreational drinking water comes entirely from outside diversion sources. The results show that the JXZ's aquatic habitat conditions (mean water temperature, total nitrogen concentration, total phosphorus concentration, and nitrogen to phosphorus ratio) are highly suitable for the proliferation of cyanobacterial biomass during the high-water period. The RUE was used for calculation and shows a strong relationship with algae density, which means that it can be used as an index to define the degree of urban river cyanobacterial blooms. The findings indicate that the risk of cyanobacterial bloom is absent when the RUE is less than 46.81; blooms appear in the water bodies when the RUE reaches up to 106.68. This work provides theoretical support for the sustainable use of regional water resources. Abstract : Lake Taihu basin river network; Algal resource availability; Eutrophication; Cyanobacterial prevention and control; Urbanization.